2022
DOI: 10.3390/jcm11041018
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Differences in Internet Gaming Disorder (IGD): From Psychological Features to Neuroanatomical Networks

Abstract: Internet gaming disorder (IGD) has been included in the 2013 Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a condition in need of further study, and gaming disorder was recognized by the World Health Organization as a mental disorder in the International Classification of Disease (ICD-11) of 2018. IGD has different characteristics in the two sexes and is more prevalent in males than females. However, even if the female gamer population is constantly growing, the majority of available studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 125 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…35,36 Moreover, abnormal frontoparietal/cingulo-opercular network connections have been described in males with IGD, suggesting another possible mechanism for male vulnerability to develop IGD. 37 Marraudino et al, 38 in their review, also examined sex/gender differences identified at the neurobiological level in individuals with IGD. Regarding the prefrontal region, a lower activation of the left dlPFC has been identified, especially in the case of women.…”
Section: Neurobiological Sex/gender Differencesmentioning
confidence: 99%
“…35,36 Moreover, abnormal frontoparietal/cingulo-opercular network connections have been described in males with IGD, suggesting another possible mechanism for male vulnerability to develop IGD. 37 Marraudino et al, 38 in their review, also examined sex/gender differences identified at the neurobiological level in individuals with IGD. Regarding the prefrontal region, a lower activation of the left dlPFC has been identified, especially in the case of women.…”
Section: Neurobiological Sex/gender Differencesmentioning
confidence: 99%
“…It mediates the salience and control of goal‐directed behavior in inhibitory processes (de Bourbon‐Teles et al, 2014 ; Phillips et al, 2016 ; Saalmann, 2014 ). Higher fractional anisotropy in the thalamus and lower functional connectivity between the thalamus and dorsal striatum have been found in IGD (Jin et al, 2016 ; Marraudino et al, 2022 ). Additionally, Greater brain activation and perfusion of the thalamus have been observed in TUD (Derogatis & Melisaratos, 1983 ; Due et al, 2002 ; Franklin et al, 2007 ; Kang et al, 2012 ; McClernon et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It mediates the salience and control of goal-directed behavior in inhibitory processes (de Bourbon-Teles et al, 2014;Phillips et al, 2016;Saalmann, 2014). Higher fractional anisotropy in the thalamus and lower functional connectivity between the thalamus and dorsal striatum have been found in IGD (Jin et al, 2016;Marraudino et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study conducted by Wartberg et al ( 8 ) found that male sex, severe self-esteem problems, and severe hyperactivity symptoms are predictors of problematic online gaming behavior. In addition to the above, several other studies focusing on risk factors for IGD support that many variables are significantly associated with the development of IGD, including video game cost ( 9 , 10 ), gaming time ( 11 , 12 ), difficulty in emotion regulation ( 13 ), higher impulsivity ( 11 , 14 , 15 ), hyperactivity symptoms ( 16 – 19 ), self-esteem problems ( 19 – 21 ), playing multiplayer games ( 22 , 23 ), emotional symptoms ( 24 , 25 ), peer relationship problems ( 26 – 28 ), family relationship problems ( 29 , 30 ), and male sex ( 2 , 12 , 31 – 33 ), among others. Therefore, we collected information on these variables, with age and lifestyle factors (which we believe may be related to family support) as candidate predictors.…”
Section: Introductionmentioning
confidence: 99%